Struktura przestrzenna drzew różnej grubości w drzewostanach sosnowych (Pinus sylvestris L.) o różnym zagęszczeniu początkowym - Szmyt, Janusz; Zabielski, Mariusz (Leśne Prace Badawcze, 2010)
An investigation was carried out on a 34-year old untended pine ( Pinus sylvestris L.) plantation in the Siemianice Forest Experimental Station. Univariate and bivariate analyses were applied using Ripley’s function to describe the spatial pattern of different tree categories. In the univariate analysis, the following tree categories were taken into consideration: all live trees, small trees (DBH < DBHaverage) and large trees (DBH > DBHaverage). The bivariate analysis focused on the spatial relationships between small and large trees. The investigated stands differed from one another in terms of the intensity of self-thinning. The poorest survival of trees occurred in the stand with the highest density (25%), and the highest survival was in the stand with the lowest density (79%). Since all stands were established by planting at a regular initial spacing, simple sequential inhibition (SSI) appeared to be the best spatial point pattern process describing the nature of tree distribution. Regularity was detected in all live trees, as well as in the trees from each size class considered. Bivariate analysis revealed segregation between the thick and thin trees in the case of stands established with square spacing, whereas in the stands established with rectangular spacing the segregation was observed only in the trees in rows. In spite of evident differences in the intensity of self-thinning between investigated stands, they did not differ with respect to the spatial pattern of live trees. The regular spatial pattern formed by the trees has resulted mostly from the initial spacing and may persist for a long time.